Effect of Andrographis paniculata on Blood Sugar Levels Through Regulation of Alpha-Glucosidase Enzyme Expression: An In Vivo Study - Rachmat Hidayat; Patricia Wulandari (HM Publisher, 2022)
Diabetes mellitus (DM) is a disease characterized by an increase in blood glucose levels caused by insulin deficiency, either absolute or relative. The α-glucosidase enzyme functions to accelerate the absorption of glucose by the small intestine by catalyzing the hydrolytic cleavage of oligosaccharides into monosaccharides. This study aims to explore the potential of AP extract in regulating blood sugar levels through inhibition of α-glucosidase activity in the intestine. This study is an in vivo experimental study. A total of 30 rats were divided into a control group and treated with Andrographis paniculata. Examination of blood sugar levels was carried out by spectrophotometry and examination of alpha-glucosidase enzymes by ELISA. Data analysis was performed using SPSS software with univariate and bivariate analysis. Andrographis paniculata extract was able to reduce blood sugar levels and was able to decrease the activity of the alpha-glucosidase enzyme as the dose increased. Andrographis paniculata extract is able to reduce blood sugar levels by inhibiting the activity of the alpha-glucosidase enzyme in the intestine.